2003
DOI: 10.1080/0892701021000053381
|View full text |Cite
|
Sign up to set email alerts
|

Coatings Based on Side-chain Ether-linked Poly(ethylene glycol) and Fluorocarbon Polymers for the Control of Marine Biofouling

Abstract: The preparation of side group modified polystyrene-based surface-active block copolymers (SABC) for use as marine fouling resistance/release applications is described. Modifying moieties such as poly(ethylene glycol) (PEG) and semifluorinated segments were used. A novel bilayer methodology has been employed that provides both suitable mechanical properties through the use of an elastomeric primer layer of styrene-ethylene/butylene-styrene (SEBS) and control of surface-chemistry through use of the SABCs. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 19 publications
2
105
0
Order By: Relevance
“…However, recent studies with polystyrenebased, surface-active block copolymers have shown that surface wettability alone cannot predict settle ment in some systems (Youngblood et al 2003). For Ulva zoospores and for cypris larvae of B. amphitrite, both hydrophilic and hydrophobic xerogel films displayed reduced settlement relative to a glass standard, which suggests that settlement Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies with polystyrenebased, surface-active block copolymers have shown that surface wettability alone cannot predict settle ment in some systems (Youngblood et al 2003). For Ulva zoospores and for cypris larvae of B. amphitrite, both hydrophilic and hydrophobic xerogel films displayed reduced settlement relative to a glass standard, which suggests that settlement Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Such inert coatings have been identified for a number of well-defined surfaces in short term, single species assays. Especially ethylene glycol (EG) x -containing coatings have been used in the biomedical area [21][22][23][24] and have recently been investigated with respect to their marine anti-fouling potential [25][26][27][28][29][30][31][32][33]. However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35].…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…However, the degradation of the ethylene-glycol-containing chemistries makes them unsuitable for long-term antifouling applications [34,35]. Other promising approaches involve the use of amphiphilic [26,27,29,36] or zwitterionic chemistries [37][38][39][40]. Even though fouling inhibition is the most desirable way of avoiding biofouling, the development of such inert, non-toxic, and long-term stable coatings remains to be the most challenging of the three approaches.…”
Section: Biofouling Research: the Quest For Environmentallymentioning
confidence: 99%
“…The present review describes the effect of mixed PEG on the non-biofouling character and also hybrid construction of a PEG/biopolymer mixture on substrate surfaces for versatile applications. Because many excellent reviews on PEG surface coating have been previously published, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] this review mainly introduces our work. BACKGROUND PEG has long been manufactured industrially and utilized in many applications such as nonionic surfactants, lubricants, an intermediate for urethane composition, adhesives and cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true regarding the versatile techniques for surface coating using PEG that have been developed since the 1980s to improve blood and bio-compatibility. Figure 1 summarizes several methods for the immobilization of PEG on substrate surfaces: PEG gels, 19,20,36 the physical and chemical immobilization of PEG 13,21,37 (so-called grafting-to method), the adsorption of block [22][23][24][25][26][27]38 and graft 27,28,39,40 copolymers, polymerization from the surface 41 (the so-called grafting-from method), the immobilization of star-shape polymers and micelles, [42][43][44] and other methods.…”
Section: Introductionmentioning
confidence: 99%